Reinforcement therapy: The consequation of asocial behavior in a children’s psychiatric hospital - Dollar, Barry L.; Sutton, Berverly (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
A treatment milieu based on the consequation of asocial behavior must consider the agents of reinforcement. The contingencies for social reinforcement must be carefully monitored if the maintenance of cooperative inter-behaviors is to be present in the patient’s receiving environment. A treatment plan is described which is designed to replace asocial aggression and competition with adaptive cooperation.